Dyslexia Dilemma - Monica Cook (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
More than 70 million Americans have learning and thinking differences, like ADHD and dyslexia - that’s 1 in 5 people who learn and think differently (Understood For All, 2014). Dyslexia is a disorder characterized by reading below the expected level for one’s age. Problems may include difficulties in reading, rhyming, spelling, identifying common words, phonetic pronunciation and comprehension, or struggle with writing assignments. This paper will examine the history of dyslexia, successful intervention programs for dyslexic learners, and discuss the need for adequate training programs for teaching personnel.